Skip to main content

What is the ideal gas equation?

The equation of state of an ideal gas is given by,


PV = nRT


Where, n is the number of moles of the gas and R is the gas constant for one mole of the gas.



The gas law


Boyle's law


If \(\mu\) and T are constant then idael gas equation becomes, $$PV = Constant $$ or $$ P \propto \frac{1}{V} $$ This is the Boyle's law.



Charle's law


If \(\mu\) and P are constant then idael gas equation becomes,
$$ V \propto T $$ This is the Charle's law.



Gay lussac's law


If \(\mu\) and V are constant then idael gas equation becomes,
$$ P \propto T $$

This is the Gay lussac's law.



Specific heat capacity


Specific heat capacity is given by,


$$ s = \frac{S}{m}$$


Where, S is heat capacity and $latex m$ is the mass of substance.


The unit of specific heat capacity is J kg-1 k-1

Degrees of freedom



Number of degrees of freedom of a system is given by following,
N = 3A - R
Where,
A is the number of particles in the system and R is the number of independent relations among the particles.




For mono atomic gases, the degrees of freedom is three.
For diatomic gases, the degrees of freedom is five.
Linear triatomic molecules has seven degrees of freedom.
A non Linear triatomic molecules has six degrees of freedom.

Popular posts from this blog

How many fundamental and supplementary units in SI?

In SI, there are seven base ( fundamental ) units and two supplementary units.
Base unit

Physical quantity


Unit


Symbol




Mass


Kilogram


kg




Length


Metre


m





Time


Second


s





Temperature


Kelvin


K





Electric current


Ampere


A





Luminous intensity


Candela


cd





Quantity of matter


Mole


mol




Supplementary units


Physical quantity


Unit


Symbol




Plane angle


Radian


rad





Solid angle


Steradian


sr



Conversion factor
Conversion of length

1 centimetre = 10-2 metre
1 millimetre = 10-3metre
1 micrometre = 10-6metre
1 nanometre = 10-9 metre
1 angstrom= 10-10 metre
1 fermi = 10-15 metre
1 kilometre = 103 metre
1 austronomical unit = 1AU=1.496 × 1011 metre
1 light year = 1 ly = 9.461 ×1015metre
1 mile = 1.609 ×103 metre
1 yard = 0.9144 metre
1 inch = 0.0254 metre


Conversion of time

1 mili second= 10-3 second
1 micro second = 10-6 second
1 neno second = 10-9 second
1 hour = 60 minute = 3600 second
1 day = 24 hours =86400 second
1 year = 365 day = 3.156× 107 second
1 sec = 10-8second


Conversion of mass

1 gram = 10 -3 kg
1 quintal = 100 kg
1 tonne = 1000 kg
1 slug = 14.59…

What is the Universal law of gravitation?

Force of attraction between two masses \(m_1\) and \(m_2\) is given by, $$ F = \frac{m_1 m_2}{r^2}$$ Where, r is the distance between two masses \(m_1\) and \(m_2\). G is a constant, called the Universal gravitational constant. That is called Universal law of gravitation. Acceleration due to gravity ( variation formula ) If a body is falling freely, under the effect of gravity, then the acceleration in the body is called acceleration due to gravity. Variation in acceleration due to gravity with height Acceleration due to gravity at a height h above the surface of earth is, $$g' = g (1 - \frac{2h}{R_e})$$ Where, Re is the radius of the earth. g is the acceleratin due to gravity. Variation in acceleration due to gravity with depth Acceleration due to gravity at a depth d below the surface of earth is, $$g' = g (1 - \frac{d}{R_e})$$ Where, Re is the radius of the earth. g is the acceleratin due to gravity. Variation in acceleration due to gravity with rotatio…

Differentiation formula

Fomulae of Differentiation d⁄dx (c) = 0   Where c is constant.d⁄dx (cx) = c   Where c is constant.du⁄dt = du⁄dx ⋅ dx⁄dtd⁄dx (u+v) = du⁄dx + dv⁄dxd⁄dx (uv) = u dv⁄dx + v du⁄dxd⁄dx ( xn ) = n xn-1  Where n is real number.d⁄dx un = n un-1du⁄dx   Where u is function of x.d⁄dx sin x = cos x d⁄dx cos x = -sin x d⁄dx tan x = sec2 x d⁄dx cot x = - cosec2 x d⁄dx sec x = tan x sec x d⁄dx cosec x = - cot x cosec x d⁄dx loge x = 1⁄xd⁄dx loge u = 1⁄udu⁄dxd⁄dx ( ex ) = exd⁄dx ( eax ) = a eaxd⁄dx sin ax = a cos ax d⁄dx sin (ax+b) = a cos (ax+b) d⁄dx cos ax = - a sin ax d⁄dx cos (ax+b) = - a sin (ax+b)